1973
DOI: 10.1007/bf01795475
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and reactions of chitinase and lysozyme on chitin

Abstract: Isotherms for adsorption of chitinase on chitin and lysozyme on chitin have been determined at two temperatures and rates of hydrolysis of chitin catalysed by these enzymes have been measured at three temperatures and at several enzyme concentrations for each. Ribonuclease, not an enzyme for chitin, and heat-denatured lysozyme and chitinase show reduced or no adsorption to this substrate.Initial hydrolysis rates of chitin by both enzymes are proportional to total enzyme concentrations in the range of concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Besides specific chitosanases, also cellulases can possess considerable chitosan-cleaving activity (Xia et al, 2008). Furthermore, lysozyme has also been shown to hydrolyze chitin, even if processivity is low when compared to true chitinases (Skujiņš et al, 1973). Cellulases can also bind directly to chitin (Ekborg et al, 2007; Li and Wilson, 2008), but there are no reports of these enzymes actually hydrolyzing the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides specific chitosanases, also cellulases can possess considerable chitosan-cleaving activity (Xia et al, 2008). Furthermore, lysozyme has also been shown to hydrolyze chitin, even if processivity is low when compared to true chitinases (Skujiņš et al, 1973). Cellulases can also bind directly to chitin (Ekborg et al, 2007; Li and Wilson, 2008), but there are no reports of these enzymes actually hydrolyzing the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The ChBD-CadA was almost completely immobilized on chitin within 10 min with a maximum specific activity of 86.33 U/mg, which was consistent with our previous result of chitinase (CmChi1) adsorption by chitin. Skujins et al (1973) reported the adsorption reaction between chitin and ChBD in chitinase was very fast and was nearly accomplished within 2 min (Skujins et al, 1973). With extended adsorption time, the concentration of protein adsorbed didn't obviously increase, nor did the specific activity or CadA activity.…”
Section: Simultaneous Purification and Immobilization Of Chbd-cada Bymentioning
confidence: 99%
“…The universal buffer: 5 M Na 2 HPO 4; 5 M H 3 BO 3; 3.6 M citric acid; 25 M NaOH; pH 5.5 or 9.5 (Skujins et al, 1973) was used in all assays.…”
Section: Enzyme Assaysmentioning
confidence: 99%